Aberrant Mesenteric Adipose Extracellular Matrix Remodelling is Involved in Adipocyte Dysfunction in Crohn's Disease: The Role of TLR-4-mediated Macrophages. (16th June 2022) - Zuo, Lugen; Li, Jing; Zhang, Xiaofeng; Geng, Zhijun; Song, Xue; Wang, Yueyue; Ge, Sitang; Shi, Ruohan; Zhou, Yueqing; Ge, Yuanyuan; Wu, Rong; Hu, Jianguo
Abstract: Background and Aims: Hypertrophic mesenteric adipose tissue [htMAT] is involved in the disease progression of Crohn's disease [CD] through expressing proinflammatory adipokines from dysfunctional adipocytes by unknown mechanism. Adipocyte function is affected by dynamic adipose tissue extracellular matrix [ECM] remodelling that is mainly mediated by macrophages, and our study aimed to reveal whether aberrant ECM remodelling was present in CD-htMAT and its effects on adipocyte dysfunction, as well as the mechanism. Methods: ECM remodelling was examined in MAT samples from CD patients and controls. Mice with dinitrobenzene sulphonic acid [DNBS]-induced colitis were used in vivo study, and lipopolysaccharide [LPS]-induced remodelling behaviour in macrophages was examined in vitro . Macrophages or TLR4 inhibition were used to analyse ECM remodelling mechanisms and their effects on adipocyte function. Results: Aberrant ECM remodelling: was observed in CD-htMAT, which was characterised by a widened and deformed ECM structure accompanied by dysregulated matrix synthesis and degradation; served as a reservoir for inflammatory factors/cells dominated by macrophages; and was involved in adipocyte dysfunction. In addition, macrophages were the main source of ECM remodelling regulatory factors with activation of Toll-like receptor 4 [TLR4] in htMAT. In vivo, macrophage depletion or TLR4 inhibition largely attenuated mesenteric ECM remodelling while improving mesenteric adipocyte dysfunction during chronic enteritis. In vitro, antagonizing TLR4 significantly inhibited LPS-induced macrophage ECM remodelling behavior. Conclusions: The aberrant ECM remodelling in CD-htMAT contributed to mesenteric adipocyte dysfunction, which may be caused at least partly by TLR4-mediated macrophage remodelling behavior. Inhibiting ECM remodelling may be a potential therapeutic strategy for CD. Graphical Abstract: In CD patients, an aberrant and ongoing ECM remodelling is present in hypertrophic MAT, which may be caused at least partly by TLR4-mediated macrophage remodelling behaviour and contribute to mesenteric adipocyte dysfunction.